Adjunctive granisetron therapy in patients with sepsis or septic shock (GRANTISS): A single-center, single-blinded, randomized, controlled clinical trial - Guan, Jianbin; Liao, Yuping; Guo, Yuexun; Yu, Shuang; Wei, Rongjuan; Niu, Mengwei; Gan, Jianwei; Zhang, Lu; Li, Tong; Lv, Jin; Shichen, Maoyou; Chang, Ping; et al. (Frontiers in Pharmacology, 2022)
Background: In preclinical experiments, we demonstrated that the 5-HT3 receptor antagonist granisetron results in reduced inflammation and improved survival in septic mice. This randomized controlled trial was designed to assess the efficacy and safety of granisetron in patients with sepsis. Methods: Adult patients with sepsis and procalcitonin >= 2 ng/ml were randomized in a 1:1 ratio to receive intravenous granisetron (3 mg every 8 h) or normal saline at the same volume and frequency for 4 days or until intensive care unit discharge. The primary outcome was 28-day all-cause mortality. Secondary outcomes included the duration of supportive therapies for organ function, changes in sequential organ failure assessment scores over 96 h, PCT reduction rate over 96 h, the incidence of new organ dysfunction, and changes in laboratory variable over 96 h. Adverse events were monitored as the safety outcome. Results: The modified intention-to-treat analysis included 150 septic patients. The 28-day all-cause mortalities in the granisetron and placebo groups were 34.7% and 35.6%, respectively (odds ratio, 0.96; 95% CI, 0.49–1.89). No differences were observed in secondary outcomes. In the subgroup analysis of patients without abdominal or digestive tract infections, the 28-day mortality in the granisetron group was 10.9% lower than mortality in the placebo group. Adverse events were not statistically different between the groups. Conclusion: Granisetron did not improve 28-day mortality in patients with sepsis. However, a further clinical trial targeted to septic patients without abdominal/digestive tract infections perhaps is worthy of consideration. Clinical Trial registration: www.clinicaltrials.gov, identifier NCT03924518.